Evolution of the regulatory framework for health care of migrants and refugees in Peru: Toward inclusive care supported by digital technologies - Galán-Rodas, Eden (2026)
Peru has experienced a sustained increase in migratory flows and asylum applications since 2017, requiring adaptations in the health system’s responses to guarantee the right to health without discrimination. This article reviews the evolution of the national and international regulatory framework applicable to the care of migrants and refugees in the country, identifies persistent gaps in effective access (irregular migration status; economic, administrative, cultural, and discrimination-related barriers), and analyzes the enabling role of digital health in delivering inclusive care. A review of laws, decrees, resolutions, and technical guidelines, as well as directives from multilateral organizations, was conducted to map progress and opportunities. The article proposes the responsible use of telehealth, interoperable electronic health records, digital identity and verification, mobile applications, and resources incorporating artificial intelligence to improve continuity of care, vaccination, mental health, and the management of chronic and infectious diseases, with due consideration of ethics, data protection, equity, and algorithmic governance. Finally, recommendations are offered to close the gap between policy and practice, strengthen interoperability, reduce administrative and economic barriers, and build digital capacities among health personnel and both migrant and host populations, as a pathway toward truly universal and sustainable coverage.